Cluburile de lectură: păstrarea stu-quoului sau nevoia reinventării - Harjevschi, Mariana (BIBLIOPOLIS, 2024)
The article addresses the methodology of organizing a reading club in public libraries: from the way it is initiated and managed, to the definition of the objectives and purpose of the club. Organizing a reading club in reading spaces can be a rewarding activity for librarians, requiring dedication, involvement and careful planning of every detail: selecting books, moderating meetings, co-opting members, promoting it, etc. During its evolution, the B. P. Hasdeu Municipal Library had in its offer of reading services various programs or actions to develop the culture of reading, to promote books and writers, including reading clubs. These have always been diverse in form and methods, interesting in content and protagonists, attractive due to the creativity of librarians.